Ecotourism Management at Teluk Tamiang Beach, Pulau Laut Tanjung Selayar, Kotabaru, South Kalimantan - Muhammad Saddam Husein; Fredinan Yulianda; Gatot Yulianto (GoAcademica Research & Publishing, 2024)
The coastal area in Teluk Tamiang Village has a relatively high potential for biological natural resources. The potential of natural resources owned by this island can be seen in the ecosystem of coral reefs, reef fish, ornamental fish, seagrass beds and fisheries. In addition to having an ecological function, this ecosystem also has a high aesthetic value for the development ofmarine tourism. The purpose of this study was to determine the suitability class and carrying capacity of marine ecotourism for snorkeling and beach activities that can be utilized in Teluk Tamiang Village, Tanjung Selayar Laut Island District, Kotabaru Regency, South Kalimantan Province. The suitability class of marine ecotourism in Teluk Tamiang was in the appropriate and very suitable category, with a capacity for snorkeling tourism activities of 681 people/day with a utilization area of 17.04 ha, and for beach tourism with a utilization area of 1000 meters, able to accommodate tourists as many as 80 people/day. Thus, the total number of tourists that can be accommodated by both types of tourism activities is 761 people/day.